The shift in the concept of power and conflict: A study in cyber wars (قضايا سياسية, 2023)
The research was attempts to diagnose the most important indicators of transformation and change which affected the concepts of power ,conflict and wars in international relations and international system in general. By identifying the most important reasons leading to that transformation in those concepts including the massive technological and information revolation>The increasing dependence on internet networks , whether by individuals or groups and the increasing international dependence on them in all areas of political and economic development and inthe military and security fields .